2018
DOI: 10.1007/s11060-017-2736-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and efficacy of lomustine and bevacizumab in recurrent glioblastoma patients

Abstract: The combination of lomustine and bevacizumab is a commonly used salvage treatment for recurrent glioblastoma (GBM). We investigated the toxicity and efficacy of lomustine plus bevacizumab (lom-bev) in a community-based patient cohort and made a comparison to another frequently used combination therapy consisting of irinotecan plus bevacizumab (iri-bev). Seventy patients with recurrent GBM were treated with lomustine 90 mg/m every 6 weeks and bevacizumab 10 mg/kg every 2 weeks. Toxicity was registered and compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 15 publications
1
29
0
2
Order By: Relevance
“…More details on administration has previously been described (40). After progression on primary therapy, 250 patients underwent reresection and 280 received bevacizumab in most cases given together with irinotecan or lomustine (CCNU) dependent on the local guidelines at the time (44). Selected patients further received different types of experimental treatment either before or after bevacizumab recurrence therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…More details on administration has previously been described (40). After progression on primary therapy, 250 patients underwent reresection and 280 received bevacizumab in most cases given together with irinotecan or lomustine (CCNU) dependent on the local guidelines at the time (44). Selected patients further received different types of experimental treatment either before or after bevacizumab recurrence therapy.…”
Section: Treatmentmentioning
confidence: 99%
“…Previously reported survival under BEV as a monotherapy or with concurrent chemotherapies (lomustine or irinotecan) is variable, with OS ranging from 4–12 months and PFS from 2.3–6 months [12,13,34,35,36,37]. The two single-arm phase II studies that enabled accelerated approval of BEV for recurrent GBM in 2009 reported survival under BEV monotherapy as 9.2 months OS and 4.2 months PFS [12], and 7.8 months OS and 4.0 months PFS, respectively [13].…”
Section: Discussionmentioning
confidence: 99%
“…The common alkylating agents used in HGG are temozolomide (Tmz, 8-Carbamoyl-3-(2-chloroethyl)imidazo (5, 1-d)-l,2,3,5-tetrazin-4(3 H)-one) ( Figure 1 ) and lomustine (chloroethyl-cyclohexyl-nitrosourea, CCNU) [ 40 , 41 , 42 ]. Before Tmz, CCNU was the first-line of treatment in GBM patients (110 mg/m 2 orally every six weeks) [ 43 ].…”
Section: Overview Of Standard Therapy In Hggmentioning
confidence: 99%